MANAJEMEN PELAYANAN HAJI DAN UMRAH KBIH NASRUL UMMAH - Rahma, Utari Nur; Sari, Dian Yunita; Afifah, Siti Nur; Sholichah, Falichatus (Institut Agama Islam Negeri Metro, 2023)
As one of the KBIH in Kediri, which has been established for more than 20 years and has served many pilgrims and Umrah pilgrims, KBIH Nasrul Ummah is not without problems in management that must be faced. Departing from these facts, researchers are interested in conducting research that aims to determine the management of Hajj and Umrah services at KBIH Nasrul Ummah. Then from the existing problems the researcher will formulate a solution that is expected to help overcome these problems. This research is qualitative research with data collection techniques in the form of observation, interview and documentation. The results showed that KBIH Nasrul Ummah was one of the KBIHs in Kediri with complete facilities and prioritizing the comfort of the congregation. In addition, the KBIH management is neatly organized and always tries to provide maximum service to the congregation. However, the congregation's training before leaving for the holy land was not equipped with qualified Arabic language training. So the researchers designed Arabic language training for the congregation with the aim of helping the congregation to be more independent and able to add positive value to KBIH Nasrul Ummah.